FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENABUNG PADA BANK SYARIAH (BANK RIAU SYARIAH CABANG PEKANBARU) - Nobel Aqualdo; Lanang Diayudha (Business Management Journal, 2017)
The background of this research on Syariah banking is based on the opinion and supposition that the interest given by conventional banking is a usury. As can be seen on the national and regional development on Syariah Banking, it is shown that the public interest in Syariah Banking is very high. This research is conducted mainly in the city of Pekanbaru on Bank Riau Syariah Pekanbaru Branch. The purpose of this research is to find out the factors often influencing the public interest in saving their money on Bank Riau Syariah. There are primary and secondary used in this research. The primary data is directly acquired from the main resources through the use of questionnaire. The secondary data used in this research is gathered with the help from Bank Riau Syariah Pekanbaru Branch, and the organizational structure of said bank. The method used in analysing the data of the research is a descriptive method which is done by following the procedure of solving the problem being investigated and by describing the state of the object of the research at the time of the research, based on the fact and reality. Then, the data collected is organized and arranged in the form of tables to be later elaborated and analysed. The result of the research shows that the dominant factors in influencing the public interest in saving their money in Bank Riau Syariah Pekanbaru Branch is to avoid act of committing usury. The other factors are profit and the belief that saving in a Syariah Bank is one form of confirming the Islamic Syariah. Moreover, there are also other factors influencing the public interest in saving in a Syariah Bank, such as accessibility, security, and other non-related factors such as the good service provided by the bank in serving its customer. Key Words- Syariah Bank, Saving, Customer